Current monitoring and treatment of progressive fibrosing interstitial lung disease: a survey of physicians in Japan, the United States, and the European Union. (1st February 2021) - Takizawa, Ayako; Kamita, Mitsutoyo; Kondoh, Yasuhiro; Bando, Masashi; Kuwana, Masataka; Inoue, Yoshikazu
Abstract: Objective: To understand assumptions about and approaches to interstitial lung disease (ILD), including those of the progressive phenotype (progressive fibrosing ILD), this multinational survey assessed physicians' attitudes toward, knowledge of, and management strategies for progressive fibrosing ILD. Methods: This internet-based survey of physicians was conducted between November 2018 and February 2019. Practical management strategies for progressive fibrosing ILD, and current approaches to the assessment and treatment of ILD, were compared between countries/regions (Japan vs. United States and European Union) and specialties (pulmonologists vs. rheumatologists). Results: The survey was completed by 574 respondents. Compared with Western countries, the progressive fibrosing phenotype concept was not widely understood by Japanese respondents, with no notable differences in the understanding of this phenotype between pulmonologists and rheumatologists. Across all regions, pulmonary function tests, diffusing capacity of the lungs for carbon monoxide assessments, and pulse oximeter measurements were commonly performed at intervals of ≤6 months. In general, physicians in the United States and European Union preferred physiologic approaches for follow-up, while those in Japan preferred imaging and blood monitoring. Compared with rheumatologists, pulmonologists performed more frequent monitoring of autoimmune ILDs, and the differences between specialties were most pronounced in Japan. Regional differences in treatment approaches were observed, probably reflecting the local availability of agents and healthcare environments. Conclusions: Awareness and management of progressive fibrosing ILD varied between specialties and regions, highlighting an unmet need for standardized diagnosis, treatment guidelines, and specialist education in this area.